Distribution Approximations for Cointegration Tests with Stationary Exogenous Regressors - H. Peter Boswijk; Jurgen A. Doornik (Tinbergen Institute, 1999)
The distribution of a functional of two correlated vector Brownian motions isapproximated by a Gamma distribution. This functional represents the limiting distribution for cointegration tests with stationary exogenous regressors, but also for cointegration tests based on a non-Gaussian likelihood. The approximation is accurate, fast, and easy to use in comparison to both tabulated critical values and simulated p-values.
Keywords: 330; Schätztheorie; Kointegration; Regression; Theorie